STUDENTS’ PERCEPTIONS ON THE USE OF E-MODULES IN BUILDING ENGINEERING EDUCATION STUDY PROGRAM - Reza Muhamad; Rosmawita Saleh; R. Eka Murtinugraha (Jurnal Pensil : Pendidikan Teknik Sipil, 2022)
This study aims to examine student perceptions of the use of e-module teaching materials in the Concrete Stone Practice course, Building Engineering Education study program, Faculty of Engineering, State University of Jakarta. This research is descriptive-quantitative research, with the data collection instrument in the form of a questionnaire. There are four indicators that are measured in knowing students' perceptions of the use of e-module teaching materials, namely the presentation of the material, language, graphics, and usefulness. The research population is Building Engineering Education students batch 2021 who take the Concrete Stone Practice course in the even semester of the 2021/2022 academic year with a research sample of 74 students. The results showed that students' perceptions of the use of the Concrete Concrete Practice e-module as a whole obtained an average of 86.39% in the very good category. This can be seen from the majority of students' perceptions showing that they agree and strongly agree with the presentation of the material, language, graphics, and benefits contained in the Concrete Stone Practice e-module that can help in the learning process. There is also supporting data, which is student score data during the learning process for the Concrete Stone Practice course, where the overall average score of 81.35 is included in the good category. Based on these results, it indicates that the concrete stone practice e-module can be used as an excellent alternative to help the student learning process in the Concrete Stone Practice course in the Building Engineering Education study program, State University of Jakarta.